Molecular Detection of Par influenza Virus 1, 2, 3 and 4 Serotypes and Immunological Response in Otitis Media Patients in Babylon-Iraq - Ayam M. Salih (Journal of Global Pharma Technology, 2017)
(AOM) occur as a case of viral upper respiratory tract infections in young children. Respiratory viruses and AOM both exhibited seasonal discrepancy. Respiratory paramyxo viruses consist of human par influenza viruses are highly distribution, cause the common of childhood croup, bronchiolitis, and pneumonia.  The study was start from6March 2016 to 20May   2016 fifty  cases of otitis media infection were detect  inpatient’s admitted  to AL- Hilla teaching hospital in Babylon - Iraq. Ear swabs and nasopharynx secretion specimens were collected for studies the viral infection detection. The results display the percentage of parainfluenza virus in AMO 22(44%) was positive from fifty cases. The results also show percentage of parainfluenza virus one; two, three, and four types   were   27.2%, 22.7%, 31.8% and 18.1% respectively the study include measurement of IL-6 cytokine by using ELISA assay. Results show elevation level of IL-6 in sera of otitis media patients comparative with control group. The highest level of IL-6 in male occur in (>5-6 year) age group it was 218.39 Pg/ml .The result also shows elevation of IL-6 level in female The highest level of IL-6 in female occur in (>6-7 year) age group it was 209 Pg/ml. Result shows significant differences comparative with control group (P ≤ 0.05).Keywords: Otitis media, Ear swabs, Nasopharyngeal secretion, Parainfluenza virus, Cytokines.